The Grendelkin and the politics of succession at Heorot: The significance of monsters in "Beowulf" - Olesiejko, Jacek (Adam Mickiewicz University, 2018)
The article considers the significance of the Grendelkin as monsters, bringing to attention the Isidorian understanding of the monster as a sign, portent, and admonition. In the original Beowulf the Grendelkin are not described as possessing many of the inhuman qualities that have been applied to them in the later critical tradition or by its translators. Isidore acknowledges in Etymologies that monsters are natural beings, whose function in the system of creation is significant. The present article considers the significance of the Grendelkin in the poem and argues that Grendel and his mother function as signs underlying themes of feud and succession in the poem. The article also brings attention to the multiple references to body parts, such as hands, and their function within the poem as synecdochic representations of the Danish body politic. The article explores the sexualised and gendered perception of the body politic in the poem.
Keywords: Beowulf; Old English poetry; Anglo-Saxon England; monster studies; medieval literature